2014
DOI: 10.1016/j.yhbeh.2013.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of vasotocin receptor mRNA in a seasonally breeding songbird

Abstract: Behaviors associated with breeding are seasonally modulated in a variety of species. These changes in behavior are mediated by sex steroids, levels of which likewise vary with season. The effects of androgens on behaviors associated with breeding may in turn be partly mediated by the nonapeptides vasopressin (VP) and oxytocin (OT) in mammals, and vasotocin (VT) in birds. The effects of testosterone (T) on production of these neuropeptides have been well-studied; however, the regulation of VT receptors by T is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…*p < 0.05. during the non-breeding season (Smith et al, 1997); in seasonally breeding sparrows, treatment with testosterone reduced song variability in non-breeding adults (Meitzen et al, 2007) and hastened song crystallization in juveniles (Whaling et al, 1995). Treatment of male white-throated sparrows with testosterone reduced OTR mRNA in the arcopallium (Grozhik et al, 2014), suggesting that OTR in this region may be associated with song variability. Our current results are consistent with this idea in that OTR in the capsular region, as well as in the arcopallium overall, appeared to decrease in males after the auditory learning phase.…”
Section: Discussionmentioning
confidence: 99%
“…*p < 0.05. during the non-breeding season (Smith et al, 1997); in seasonally breeding sparrows, treatment with testosterone reduced song variability in non-breeding adults (Meitzen et al, 2007) and hastened song crystallization in juveniles (Whaling et al, 1995). Treatment of male white-throated sparrows with testosterone reduced OTR mRNA in the arcopallium (Grozhik et al, 2014), suggesting that OTR in this region may be associated with song variability. Our current results are consistent with this idea in that OTR in the capsular region, as well as in the arcopallium overall, appeared to decrease in males after the auditory learning phase.…”
Section: Discussionmentioning
confidence: 99%
“…In birds, the AVT cells are distributed in two separate cell corridors (galliformes: Aste et al 1998; passerines: Panzica et al 1999), one medial (with magnocellular and parvocellular cells) which appears to partly overlap and/or neighbor caudally our preoptic BSTM, and another one lateral (with magnocellular cells) which appears to correspond to our hypothalamic BSTM. These two cell corridors are also visible by expression of vasotocin receptors in zebra finches and other songbirds (Leung et al 2011; Grozhik et al 2014). In these studies, only the medial corridor is called BSTM, but the lateral one has been suggested to be part of this nucleus (Fig.…”
Section: Medial Extended Amygdala (Eame)mentioning
confidence: 97%
“…However, short photoperiod-induced anestrus female Syrian hamsters have lower V1aR binding in the medial preoptic nucleus, MPOA, LH, CeA, and BNST compared to females on a long photoperiod (Caldwell and Albers, 2004b), suggesting gonadal hormonal control of V1aR in various brain regions of both male and female hamsters. Furthermore, testosterone treatment increased vasotocin V1aR binding in nuclei of the song system in female canaries (Voorhuis et al, 1988) and male white-throated sparrows (Grozhik et al, 2014). …”
Section: Sex Differences In Vasopressin and Oxytocin Receptors In mentioning
confidence: 99%